Acute respiratory compromise on hospital wards: Association between recent ICU discharge and outcome. (November 2019) - Berg, Katherine M.; Donnino, Michael W.; Andersen, Lars W.; Moskowitz, Ari; Grossestreuer, Anne V.; ,
Abstract: Introduction: Acute respiratory compromise (ARC), respiratory distress requiring emergent assisted ventilation, has a mortality of 20–40%. The relationship between recent discharge from an intensive care unit (ICU) and outcomes of patients suffering ARC on hospital wards is not well known. We hypothesized that a significant percentage of ARC events would occur in patients recently discharged from an ICU, that these patients would have worse outcomes than those without prior ICU stays, and that weekend ICU discharge would be associated with higher than expected post-ICU ARC frequency. Methods: Using the Get-With-The-Guidelines-Resuscitation ARC registry, we included adult, index ARC events occurring on hospital wards. Our primary analysis used multivariable logistic regression accounting for clustering by hospital to examine the association between prior ICU discharge and survival after an ARC event. Results: Of 11, 800 ARCs, 937 (8%) occurred within two calendar days and 1010 (9%) >two calendar days after an ICU discharge. Patients with ICU discharge within two days had higher survival compared to those with no prior ICU stay (odds ratio 1.28 (95% CI: 1.11–1.48, p = 0.001)). Survival was not different in those with an ICU discharge more than two days prior and no prior ICU stay. Patients with ARC within two days of ICU discharge were not more likely to have left the ICU on a weekend. Conclusions: Contrary to our hypothesis, discharge from an ICU within two calendar days was associated with better odds for survival compared to no prior ICU discharge or ICU discharge more than two days prior.